Studies of reduced graphene oxide (rGO)/CuS nanocomposite for supercapacitor applications - Singhal, R.; Thorne, D.; Chaudhary, M.; Kumar, A.; Bhardwaj, S.; Abazi, R.; Colon, A.; Gupta, R.K.; Scanley, J.; Broadbridge, C.C.; Singh, B.P.; LeMaire, P.K.; et al. (AIP Advances, 2023)
We have prepared CuS and CuS-rGO nanocomposites via the hydrothermal method. The physical properties of the synthesized materials were studied through x-ray diffraction and scanning electron microscopy. The supercapacitor characteristics were evaluated by cyclic voltammetric and galvanostatic charge–discharge studies. The cyclic voltammetric studies conform the pseudocapacitive nature of CuS and CuS-rGO electrodes. The specific capacitance of CuS was obtained as 207, 150, and 97 F/g at a current density of 0.5, 5, and 20 A/g, respectively. The rGO-CuS nanocomposite showed improved specific capacitance of 350, 251, and 149 F/g at current densities of 0.5, 5, and 20 A/g, respectively. © 2023 Author(s).
Keywords: dept.phy; peer-reviewed